PENGARUH KOMUNIKASI ORGANISASI TERHADAP EFEKTIVITAS KERJA PEGAWAI PDAM TIRTA MEDAL SUMEDANG - Arip Rahman Sudrajat; Muhamad Dony Ardiansyah; Yayat (JRPA - Journal of Regional Public Administration, 2019)
This study aims to determine the effect of communication on employee work effectiveness at PDAM Tirta Medal, Sumedang Regency and to determine the relationship between communication and employee work effectiveness at PDAM Tirta Medal, Sumedang Regency. In this study, researchers used survey research methods, while data collection techniques were carried out through library research and field studies consisting of observation, and distributing questionnaires. The collected data is then processed and analyzed through validity test, reliability test, percentage test, normality test, correlation coefficient test, significance test, and coefficient of determination test. The population in this study were 40 employees of PDAM Tirta Medal, Sumedang Regency. For sampling, the technique of disproportionate stratified random sampling was used. The number of samples in this study were 35 people. Communication at PDAM Tirta Medal, Sumedang Regency reached 72.86%. This is included in the good category, so H0 which reads "Work communication at PDAM Tirta Medal Sumedang Regency reaches less than 75%" is accepted, and Ha which reads Work communication at PDAM Tirta Medal Sumedang Regency reaches greater than or equal to 75 %" rejected. The effectiveness of employee work on work communication at PDAM Tirta Medal, Sumedang Regency reached 70.49%. This is included in the good category because it is at an interval of 50% - 75%. So Ho which reads "employee work effectiveness on work communication at PDAM Tirta Medal, Sumedang Regency reaches less than 75%" is accepted, and Ha which reads "employee work effectiveness on work communication at PDAM Tirta Medal, Sumedang Regency reaches greater than or equal to 75 %" rejected. The positive relationship between Communication and Employee Work Effectiveness is at the Correlation level with a correlation coefficient of 0.847 with a t count of 5.73 and a t table value of 1.68. So t count is greater than t table ( t count > t table ). Thus H0 : p = 0 which states that there is no relationship between communication and work effectiveness at PDAM Tirta Medal, Sumedang Regency is declared rejected. Ha : p 0 which states that there is a relationship between communication and the work effectiveness of employees at PDAM Tirta Medal, Sumedang Regency is declared accepted. The influence of communication on the effectiveness of employee work reaches 71.74%. So the hypothesis proposed H0: p = 0 which states that there is no significant effect between communication and work effectiveness of employees at PDAM Tirta Medal, Sumedang Regency is declared rejected. While Ha: p 0 which states that there is a significant influence between discipline and work effectiveness of employees at PDAM Tirta Medal, Sumedang Regency is accepted